Controversies and Advances in Managing the Dislocated Knee - Shuman, Jill (MD Conference Express, 2015)
In this hands-on, case-based session, 4 orthopedic surgeons presented clinical pearls and case studies that illustrated complex knee injuries in high-level athletes, diagnosis and management of injuries to the posterolateral corner, factors affecting knee reconstruction of the morbidly obese, and reconstruction of the anterior cruciate ligament.